Non-detection of mycoviruses in amphibian chytrid fungus (Batrachochytrium dendrobatidis) from Australia. Issue 1 (January 2022) - Webb, Rebecca J.; Roberts, Alexandra A.; Wylie, Stephen; Kosch, Tiffany; Toledo, Luís Felipe; Merces, Marcia; Skerratt, Lee F.; Berger, Lee
Abstract: Mycoviruses may influence the pathogenicity of disease-causing fungi. Although mycoviruses have been found in some chytrid fungi, limited testing has not detected them in Batrachochytrium dendrobatidis ( Bd ), the cause of the devastating amphibian disease, chytridiomycosis. Here we conducted a survey for mycovirus presence in 38 Bd isolates from Australia (n = 31), Brazil (n = 5) and South Korea (n = 2) with a combination of modern high-throughput sequencing and conventional dsRNA cellulose chromatography. Mycoviruses were not detected in any isolates. This result was unexpected, given the long evolutionary history of Bd, as well as the high prevalence of mycoviruses in related fungal species. Given our widespread sampling in Australia and the limited number of Bd introductions, we suggest that mycoviruses are uncommon or absent from Australian Bd . Testing more isolates from regions where Bd originated, as well as regions with high diversity or low fungal virulence may identify mycoviruses that could aid in disease control. Highlights: A wide range of B.dendrobatidis isolates were screened for evidence of mycovirus infection. No mycoviruses were detected in any of the samples. The Australian Batrachochytrium dendrobatidis population may be free of mycoviruses